Ted Hughes's and Fay Godwin's Elmet: the remains of photography. Issue 3 (2nd July 2016) - Nott, Michael
Abstract: Collaborations between poets and photographers became increasingly common in the late twentieth century. Among the most successful was Remains of Elmet (1979), by photographer Fay Godwin and poet Ted Hughes. Fifteen years later, Godwin and Hughes published the revised edition Elmet (1994), which incorporated more than a third new poems and photographs into an entirely new arrangement. This article explores the thematic and formal differences between the two editions; discusses how the combination of poem and photograph stages the relationship between nature and culture; and examines how the changing collaborative relationship between Godwin and Hughes led in the revised edition to a symbiotic rather than an illustrative interaction between poem and photograph.